PENGARUH E-TRUST DAN E-SERVICE QUALITY TERHADAP E-LOYALTY MELALUI E-SATISFACTION (Studi pada Konsumen Fashion E-Commerce Shopee) - Zia Hanera (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2020)
This research was aimed to find out the effect of e-trust, e-service quality on loyalty through e-satisfaction to online customer of Shopee. This research applies the explanatory type with quantitative approach. The population in this study were customer of Shopee. The sampling technique in this study is accidental sampling with a sample of 385 respondents. The data were obtained from questionnaire through likert scale. Analysis of this research data using path analysis. Based on the results of the research and data analysis, e-trust, e-service quality has significant effect on the variable of e-satisfaction level, and e-trust, e-service quality, and e-satisfaction has significant effect on the variable of e-loyalty. Further support is needed to be able to understand consumer behavior in conducting online transaction. E-service quality factor become the biggest factor that influence customer satisfaction in online transactions, as well as the suitability in shaping e-loyalty.